Edmund G. Brown Presidential Campaign kickoff event letter - Hon. WM. A. Munnell::::::; Hon. Hugo Fisher::::::; Don Rose::::::; Joseph L. Wyatt:::::: (1960)
A letter to the Democratic Presidential Campaign Committee inviting them to Governor Edmund G. Brown's presidential campaign kickoff event in Los Angeles, California.